A new home energy management algorithm with voltage control in a smart home environment - Elma, Onur; Selamogullari, Ugur Savas (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
Energy management in electrical systems is one of the important issues for energy efficiency and future grid systems. Energy management is defined as a HEM (home energy management) on the residential consumer side. The HEM system plays a key role in residential demand response applications. In this study, a new HEM algorithm is proposed for smart home environments to reduce peak demand and increase the energy efficiency. The proposed algorithm includes VC (voltage control) methodology to reduce the power consumption of residential appliances so that the shifting of appliances is minimized. The results of the survey are used to produce representative load profiles for a weekday and for a weekend. Then, case studies are completed to test the proposed HEM algorithm in reducing the peak demand in the house. The main aim of the proposed HEM algorithm is to minimize the number of turned-off appliances to decrease demand so that the customer comfort is maximized. The smart home laboratory at Yildiz Technical University, Istanbul, Turkey is used in case studies. Experimental results show that the proposed HEM algorithm reduces the peak demand by 17.5% with the voltage control and by 38% with both the voltage control and the appliance shifting. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Home energy management; Demand response; Customer comfort; Smart home; Energy efficiency; Voltage control; DEMAND-SIDE MANAGEMENT; REDUCTION; IMPLEMENTATION; CONSUMPTION; Thermodynamics; Energy & Fuels